Advances in the understanding of disease mechanisms of autoimmune neuromuscular junction disorders. Issue 2 (February 2022) - Huijbers, Maartje G; Marx, Alexander; Plomp, Jaap J; Le Panse, Rozen; Phillips, William D
Summary: Muscle weakness and fatigue are the hallmarks of autoimmune neuromuscular junction disorders. Although a plethora of immunosuppressive treatments exist, no cure is available to date and many patients are left with debilitating muscle weakness. Recent advances in the understanding of the structure and function of the neuromuscular junction, and the development of novel in vitro and in vivo models, have been instrumental in unravelling the pathophysiology of these autoimmune diseases. These advances are providing the rationale for the development of new therapeutic strategies. Restoration of the immune imbalance in these diseases, in parallel with symptomatic therapeutic approaches at the neuromuscular junction, will be crucial to obtain long-term remission or even cure.